2002
DOI: 10.1046/j.1524-4725.2002.01205.x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Rosacea

Abstract: Simple interventions such as disease recognition and treatment, proper wound care and suture selection, as well as patient counseling have proven beneficial in optimizing surgical outcomes in the rosacea patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Weber and Moody recommended using nonpetrolatum-based ointments in patients with rosacea to prevent separation of wound edges and excessive debris along the incision. 3 Our patient was given erythromycin ointment that contains mineral oil and white petrolatum, which could have partially contributed to her postoperative symptoms and exacerbation of occult rosacea.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Weber and Moody recommended using nonpetrolatum-based ointments in patients with rosacea to prevent separation of wound edges and excessive debris along the incision. 3 Our patient was given erythromycin ointment that contains mineral oil and white petrolatum, which could have partially contributed to her postoperative symptoms and exacerbation of occult rosacea.…”
Section: Discussionmentioning
confidence: 91%
“…While little is written about the effects of rosacea on wound healing, 1 author has reported that rosacea can be exacerbated by local surgical trauma resulting in lumpy or beaded incision lines and telangiectasias along the incision line. 3…”
Section: Discussionmentioning
confidence: 99%